The Impact of Electronic Word of Mouth on Consumer Purchase Intention in Saudi Arabia E-Commerce Fashion Market: Exploring Trends, Credibility, and Social Media Influence - Edrees, Manal Elzien Abdelwahap (International Review of Management and Marketing, 2025)
This research aims to explore the impact of electronic word of mouth (EWOM) on consumer purchase intention (CPI) in Saudi Arabia’s fashion e-commerce sector. It also investigates whether brand image and social media characteristics mediate the EWOM-CPI relationship. A quantitative survey of 600 online fashion consumers across Saudi Arabia was conducted, using R statistical software for analysis. Pearson’s correlation coefficient assessed direct relationships, while the Large Sample Wald Test and General Linear Model examined mediating effects. Results showed significant correlations between EWOM factors—credibility, perceived quality, consumer engagement, and trust—and CPI. Brand image and social media features were found to mediate the EWOM-CPI relationship. This study contributes to existing literature by highlighting the mediating roles of brand image, social media attributes, and engagement in EWOM and CPI, providing new insights from Saudi Arabia’s e-commerce landscape. Given the scarcity of similar studies in the Arab region, the research is significant and proposes a framework for future studies. The findings offer valuable implications for marketers and consumer behavior analysts, aiding in the development of effective digital marketing strategies that leverage EWOM to enhance CPI in Saudi Arabia, along with practical recommendations for fashion sector professionals.